"You see, we women, we can't talk, we can't have an opinion…". The coloniality of gender and childbirth practices in Indigenous Wixárika families. (May 2020) - Gamlin, Jennie B.
Abstract: How women make decisions about care-seeking during pregnancy and childbirth, is a key determinant of maternal and child health (MCH) outcomes. Indigenous communities continue to display the highest levels of maternal and infant mortality in Mexico, a fact often accounted for by reference to inadequate access to quality services. A growing body of research has identified gender inequality as a major determinant of MCH, although this has rarely been situated historically in the context of major social and epistemological shifts, that occurred under colonialism. I used a feminist ethnography to understand the structural determinants of Indigenous maternal health. I drew on research about the colonial and post-colonial origins of ethnic and gender inequality in Mexico and specifically the Wixárika Indigenous region, in order to identify the different ways in which women have historically been disadvantaged, and the processes, situations and interaction dynamics that emerged from this. Sixty-four Wixárika women were interviewed while pregnant, and followed up after the birth of their child between January 2015 and April 2017. These data were triangulated with structured observations and key informant interviews with healthcare providers, teachers, community representatives and family members. The findings suggest that gender inequalities were introduced with the colonial system for governing Indigenous regions, and became naturalised as Wixárika communities were increasingly integrated into the Mexican nation. The associated structures of marriage, community and interpersonal relationships now operate as forms of institutionalised gender oppression, to increase Indigenous women's vulnerability, and influence decisions made about care and childbirth. Ethnographic data analysed in historical context evidence the continuity of colonial forms of inequality, and their impact on wellbeing. While welfare and health programmes increasingly aim to address gender inequality on social and relational levels, by rebalancing gendered household dynamics or empowering women, the historical and colonial roots of these inequalities remain unchallenged. Highlights: Evidences link between colonialism and gender inequality in Wixárika communities. Reveals how maternal outcomes are influenced by gender violence and polygyny. Reproblematises maternal and infant death as the Afterlife of Colonialism. Argues that decolonial approaches can improve indigenous health.